Frontotemporal dementia: clinical, neuroimaging, and molecular biological findings in 6 patients - Jauß, Jan Marek; Herholz, K.; Kracht, L.; Pantel, Johannes; Hartmann, Tobias; Jensen, M.; Essig, Marco; Schröder, Johannes (European archives of psychiatry and clinical neuroscience, 2001)
Establishing the diagnosis in patients with clinical signs and symptoms suggesting primary degenerative disease with marked frontal lobe involvement is difficult. Neuroimaging methods, in particular positron emission tomography (PET) with the tracer 18fluoro-2-deoxyglucose (FDG) and cerebrospinal fluid (CSF) examination of β-amyloid and tau-protein levels may give additional information. We report five patients with clinical and radiological features of degenerative dementia with predominantly frontal involvement and one patient with primary progressive aphasia Diagnostic work-up included computed tomography (CT), magnetic resonance imaging (MRI), PET and tau-protein and β-amyloid level determination in CSF. While neuropsychological performance varied among patients, CT and MRI demonstrated persistently frontal lobe involvement. PET revealed corresponding changes with frontal hypometabolism, but in addition, four patients (among them two with no corresponding temporal changes in CT or MRI) showed a decreased glucose uptake in the temporal cortices. CSF samples from five patients revealed elevated β-amyloid 1-42 and tau levels in three and two patients, respectively. Reduced β-amyloid 1-40 was found in two patients. We conclude that occurrence of clinical symptoms of frontotemporal dementia is accompanied by frontal hypometabolism regardless of additional clinical findings. The value of determination of β-amyloid and tau protein levels remains to be determined.
Gesehen am 25.01.2021